The Application and Prospect of Mobile Health (mHealth) in Health Service for Older People Living Alone in Community: A Narrative Review - Dehui Kong; Jingjing Fu; Yan Hong; Siqi Liu; Yu Luo (Iranian Journal of Public Health, 2022)
As a result of improvements in life expectancy and reductions in fertility rate, the increasing world population ageing brings huge challenges for both developed and developing countries. Such factors as fewer children, migration of children and widowhood further increase the number of older people living alone. Older adults prefer age in place, which means care in the home. As the main place older people live in, care in community absolutely needs more attention. Optimizing health services for the elderly living in community is of positive significance to health promotion and happiness enhancement. But the traditional health service for the elderly has drawbacks of poor timeliness and high labor cost. The rapid development of modern science and technology make it possible to apply mHealth in health service for the elderly. At present, mHealth is relatively mature in the communities of developed countries. This article presents the application of mHealth in many developed countries, as references for developing countries.